Transcriptome profiling reveals the underlying mechanism of grape post-harvest pathogen Penicillium olsonii against the metabolites of Bacillus velezensis - Zhang, Tingfu; Wen, Guoqin; Song, Bo; Chen, Zhenyong; Jiang, Shijiao (Frontiers in Microbiology, 2023)
Pathogen infection influences the postharvest shelf life of grape berries. In a preliminary study, metabolites produced by Bacillus velezensis significantly inhibited the growth of the grape postharvest pathogen Penicillium olsonii. To investigate the mechanism of interaction between B. velezensis and P. olsonii, a draft genome was generated for P. olsonii WHG5 using the Illumina NovaSeq platform, and transcriptomic changes in WHG5 were analyzed in response to exposure to B. velezensis metabolites (10% v/v). The expression levels of genes associated with sporulation, including GCY1, brlA, and abaA, were downregulated compared with those of the control. In addition, spore deformation and abnormal swelling of the conidiophore were observed. Expression of crucial enzymes, including fructose 2,6-bisphosphate and mannitol-2-dehydrogenase, was downregulated, indicating that the glycolytic pathway of WHG5 was adversely affected by B. velezensis metabolites. KEGG pathway enrichment analysis revealed that glutathione metabolism and the antioxidant enzyme system were involved in the response to B. velezensis metabolites. Downregulation of the pathogenesis-related genes PG1 and POT1 suggested that B. velezensis metabolites decreased the pathogenicity of P. olsonii. Bacillus velezensis metabolites disrupted the homeostasis of reactive oxygen species in P. olsonii by affecting glucose metabolism, resulting in spore deformation and disruption of growth. In addition, the expression of key pathogenesis-related genes was downregulated, thereby reducing the pathogenicity of P. olsonii. This study provides insights into the responses of P. olsonii to B. velezensis metabolites, and identified potential target genes that may be useful in biocontrol strategies for suppression of postharvest spoilage in grape.